Common Variable Immunodeficiency-Associated Cancers: The Role of Clinical Phenotypes, Immunological and Genetic Factors - Bruns, Luzia; Panagiota, Victoria; von Hardenberg, Sandra; Schmidt, Gunnar; Adriawan, Ignatius Ryan; Sogka, Eleni; Hirsch, Stefanie; Ahrenstorf, Gerrit; Witte, Torsten; Schmidt, Reinhold Ernst; Atschekzei, Faranaz; Sogkas, Georgios (Frontiers in Immunology, 2022)
Objective The aim of this study was to investigate the prevalence of cancer and associating clinical, immunological, and genetic factors in a German cohort of patients with common variable immunodeficiency (CVID). Methods In this retrospective monocenter cohort study, we estimated the standardized incidence ratio (SIR) for different forms of cancer diagnosed in CVID patients. Furthermore, we evaluated the likely association of infectious and non-infectious CVID-related phenotypes with the diagnosis of cancer by calculation of the odds ratio. The genetic background of CVID in patients with cancer was evaluated with sequential targeted next-generation sequencing (tNGS) and whole-exome sequencing (WES). Patients’ family history and WES data were evaluated for genetic predisposition to cancer. Results A total of 27/219 patients (12.3%) were diagnosed with at least one type of cancer. Most common types of cancer were gastric cancer (SIR: 16.5), non-melanoma skin cancer (NMSC) (SIR: 12.7), and non-Hodgkin lymphoma (NHL) (SIR: 12.2). Immune dysregulation manifesting as arthritis, atrophic gastritis, or interstitial lung disease (ILD) was associated with the diagnosis of cancer. Furthermore, diagnosis of NMSC associated with the diagnosis of an alternative type of cancer. Studied immunological parameters did not display any significant difference between patients with cancer and those without. tNGS and/or WES yielded a definite or likely genetic diagnosis in 11.1% of CVID patients with cancer. Based on identified variants in cancer-associated genes, the types of diagnosed cancers, and family history data, 14.3% of studied patients may have a likely genetic susceptibility to cancer, falling under a known hereditary cancer syndrome. Conclusions Gastric cancer, NMSC, and NHL are the most frequent CVID-associated types of cancer. Manifestations of immune dysregulation, such as arthritis and ILD, were identified as risk factors of malignancy in CVID, whereas studied immunological parameters or the identification of a monogenic form of CVID appears to have a limited role in the evaluation of cancer risk in CVID.